Konsistensi Putusan Hakim dalam Penghapusan Merek oleh Pihak Ketiga: Tinjauan UU No. 20 Tahun 2016 dan Prinsip Hizf al-mal Hukum Islam - Oetami, Rizky Amaliah; Sudiro, Amoury Adi (Tasyri' : Journal of Islamic Law, 2025)
This study discusses the consistency of judges' decisions in trademark removal cases filed by interested third parties based on Article 74 paragraph (1) of Law Number 20 of 2016 concerning Trademarks and Geographical Indications. This study uses a juridical-normative approach with a comparative method of six commercial court decisions that have similar legal substance, but produce different rulings. These inconsistencies are problematic in the context of legal certainty and protection of intellectual property rights. In the perspective of Islamic law, the abolition of a trademark that has not been used for three years without stopping can also be analyzed through the principle of maqāṣid al-sharī'ah, specifically the principle  of ḥifẓ al-māl (protection of property). Trademarks as intangible assets are part of assets that must be protected from attempts to impersonate them, forgery, or fictitious registrations. By adding the dimension of Islamic law, this study finds that trademark protection is not only relevant within a positive legal framework, but also in line with the purpose of sharia to preserve property rights and prevent tyranny in commercial transactions. These findings recommend harmonization between positive law and Islamic legal values in the settlement of trademark rights disputes.